Quality, Consistency, and Engagement as Determinants of Consumer Conversion Intention in TikTok Affiliate Marketing - Derah Sudjaniah; Junef Ismaliyanto (Penerbit Goodwood, 2026)
Purpose: This study analyzes the effects of digital marketing quality and content consistency on consumers’ conversion intention in TikTok affiliate marketing, with digital consumer engagement as a mediating variable and customer experience orientation as a moderating variable. Methodology/approach: A quantitative approach was employed using a survey of 388 TikTok users who had purchased through affiliate links. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Results/findings: The results indicate that digital marketing quality and content consistency significantly influence conversion intention, both directly and indirectly through digital consumer engagement. Engagement serves as a critical mechanism that enhances the effectiveness of digital marketing strategies. Moreover, customer experience orientation moderates the relationship between engagement and conversion intention, suggesting that a positive digital experience increases the likelihood of conversion. Limitations: This study focuses on TikTok users and affiliate marketing contexts; thus, the results may not be fully generalizable to other social commerce platforms. Conclusions: The findings highlight the importance of optimizing digital marketing quality, maintaining content consistency, and fostering consumer engagement to strengthen conversion intention. Customer experience orientation plays a vital moderating role, reinforcing engagement outcomes in digital commerce. Contributions: This study advances Consumer Engagement, Information Processing, and Customer Experience theories through an integrated mediation–moderation model of consumer conversion mechanisms. Practically, it offers guidance for brands and creators to enhance the effectiveness of affiliate marketing strategies.